The official guide to scleral lens terminology. Issue 6 (December 2020) - Michaud, Langis; Lipson, Michael; Kramer, Elise; Walker, Maria
Abstract: Purpose: In absence of scleral lens standards, this article aims to provide an official definition of terms related to scleral lens fitting and manufacturing, in order to make more uniform the use of appropriate terms when describing, writing or lecturing about scelral lenses. Adoption of a common terminology may also favor more fruitful exchanges between eyecare practitioners and manufacturers. Methods: A committee of 12 advances scleral lens clinicians met and develop a list of terms related to scleral lens fit and manufacturing. Litterature review was made using PubMed database with the keywords "scleral lenses" and "terminology". Other related publications such as textbooks were also considered valid references. Validation of the terms selected and their suggested definition was made by consultation of other experts in the field, over 2 years. A final version was adopted by the Scleral Lens Education Society late in 2018. Results: This article contains three main sections. Section I provides the definition of a scleral lens. Section II addresses the general terminology habitually applied to contact lens field but in the context of scleral lens usage. Finally, Section III suggests a decription of terms specifically used when fitting or manufacturing scleral lenses. At the end, recommendations are made to manufacturers about the essential elements to provide to eyecare practitioners in order to help them understanding the lens design and to customize their fit. Conclusion: A common language is key to advancing the science and clinical practice of scleral lens fitting. The current terminology will help standardize this field, helping eyecare practitioners, educators, speakers and manufacturers to talk with the same language.